Do autismo a Síndrome de Asperger e de volta: uma análise documental dos manuais estatísticos diagnósticos e do Código Internacional de Doenças (1980-2013) a partir da História da Ciência - Nascimento, Caio (2024)
The subject of psychodiagnoses has been widely discussed in psychology for many decades. Specifically in the case of autism, several identifications have been attributed, especially to children, due to behavioral characteristics that have led to academic, medical and social impasses regarding the accuracy of diagnoses. What was once known as Asperger's syndrome, its peculiarities and the contestation of the term have come to light. Against this backdrop, this study investigates the process of removing the term Asperger's Syndrome from the American Psychological Association's diagnostic statistical manual. Through a documentary analysis of the Diagnostic and Statistical Manual of Mental Disorders (DSM) and the International Classification of Diseases (ICD) up to 2013, together with the academic production relating to the period, we sought to establish a historical path capable of observing these changes. The observation of the documents aims to incite relevant debates in the history of psychology and psychiatry, in view of the need for a critical approach to the process of determining and constantly reformulating diagnoses in the field of mental health